THE IMPACT OF LOANWORDS ON THE DEVELOPMENT OF THE ENGLISH LANGUAGE - Baxtiyorova Lola Otabekovna (Лучшие интеллектуальные исследования, 2024)
Annotation. This comprehensive article delves into the profound impact of loanwords on the evolution and development of the English language. The classification of loanwords based on their origins provides a structured insight into the diverse linguistic sources that have contributed to English vocabulary enrichment. By addressing the controversies surrounding the incorporation of loanwords, the article delves into the complex interplay between linguistic purism and language evolution, presenting a balanced view of the ongoing debate on borrowing foreign terms. Additionally, the exploration of future trends hints at the continued integration of loanwords in line with technological advancements and globalization, underscoring English's adaptability and global relevance. The conclusion encapsulates the essence of the article, emphasizing the pivotal role of loanwords in shaping the dynamic nature of English and fostering intercultural communication. Overall, this annotation commends the article for its thorough analysis and insightful commentary on the significance of loanwords in the perpetual evolution of the English language.